(untitled) (Al-Farooq Journal of Sciences, 2026)
This paper aimed to analyze the role of environmental education in shaping sustainable behavior and supporting the green economy. It reviewed the theoretical framework of key concepts, mechanisms of influence, field applications, and challenges to its implementation. The paper adopted an inductive analytical methodology through a systematic review of several recent and peer-reviewed studies, as well as reports from relevant international organizations such as UNESCO and the OECD. The results showed that environmental education has a strong positive impact on promoting environmental values ​​and pro-environmental behavior. However, there are clear gaps in the integration of green education principles into school curricula, weaknesses in teacher training, and limited green infrastructure in educational institutions. The results also revealed that environmental education is a fundamental pillar for preparing the workforce for the green economy and achieving the Sustainable Development Goals, particularly Goals 7, 8, 12, and 13. The paper concluded that it is necessary to develop curricula, teacher training programs, and school infrastructure, and to strengthen institutional partnerships to activate the role of environmental education in the transition to a green economy and a sustainable society.